JUNIOR HIGH SCHOOL STUDENTS' PERCEPTIONS OF DIGITAL TASK-BASED LEARNING FOR ENHANCING DESCRIPTIVE WRITING SKILLS - Gunawan, Ivonie; Pambayun, Rizki Nurfida (Universitas PGRI Palembang, 2025)
This study explores students' perceptions of task-based digital learning using Padlet to enhance descriptive writing skills. Conducted in a Catholic private school in West Java, the qualitative research involved six seventh-grade English as a second language learners (three high-scoring and three low-scoring) selected from a class of 22 students. Data were collected through face-to-face interviews after students completed descriptive writing tasks on Padlet. Findings revealed positive perceptions of Padlet’s multimedia tools, with students acknowledging that features such as images, videos, and GIFs improved their ability to write descriptively and organize ideas. Students also highlighted enhanced interaction and collaboration during tasks. Despite the benefits, some challenges in using Padlet were noted. The study contributes to educational technology and language learning by showcasing Padlet’s potential to foster creativity, collaboration, and multimedia integration in writing tasks. It provides valuable insights for K-12 and higher education curriculum design, teacher training programs, and the development of user-friendly digital learning tools.